2009
DOI: 10.1016/j.jcis.2009.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Removal of phosphate from water by a Fe–Mn binary oxide adsorbent

Abstract: a b s t r a c tPhosphate removal is important in the control of eutrophication of water bodies and adsorption is one of the promising approaches for this purpose. A Fe-Mn binary oxide adsorbent with a Fe/Mn molar ratio of 6:1 for phosphate removal was synthesized by a simultaneous oxidation and coprecipitation process. Laboratory experiments were carried out to investigate adsorption kinetics and equilibrium, in batch mode. The effects of different experimental parameters, namely contact time, initial phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
159
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 386 publications
(179 citation statements)
references
References 37 publications
(43 reference statements)
19
159
0
1
Order By: Relevance
“…The elevated f-potential due to Mn 2+ enrichment benefited the adsorption of negatively-charged Sb(OH) 6 À , which was the main Sb(V) species over a wide pH range of 3-9. The positive electrostatic effect of Mn 2+ on the adsorption of arsenic and phosphate has been reported before (Zhang et al, 2007(Zhang et al, , 2009Stumm and Morgan, 1996). Mn 2+ contributed to a more significant f-potential increase for Mn-oxide, and the more remarkable effect on Sb(V) adsorption was observed thereafter.…”
Section: F-potential Variation After Adsorbing Sb(v) and Mn 2+supporting
confidence: 68%
See 1 more Smart Citation
“…The elevated f-potential due to Mn 2+ enrichment benefited the adsorption of negatively-charged Sb(OH) 6 À , which was the main Sb(V) species over a wide pH range of 3-9. The positive electrostatic effect of Mn 2+ on the adsorption of arsenic and phosphate has been reported before (Zhang et al, 2007(Zhang et al, , 2009Stumm and Morgan, 1996). Mn 2+ contributed to a more significant f-potential increase for Mn-oxide, and the more remarkable effect on Sb(V) adsorption was observed thereafter.…”
Section: F-potential Variation After Adsorbing Sb(v) and Mn 2+supporting
confidence: 68%
“…By comparison, the adsorption of Sb(V) decreased the pH iep values, which were 3.2 for FMBO and 3.0 for Mn-oxide. The remarkable shift in pH iep indicated the occurrence of specific adsorption and the formation of surface complexes in the adsorption of Mn 2+ and Sb(V) (Zhang et al, 2009;Hsia et al, 1994). The elevated f-potential due to Mn 2+ enrichment benefited the adsorption of negatively-charged Sb(OH) 6 À , which was the main Sb(V) species over a wide pH range of 3-9.…”
Section: F-potential Variation After Adsorbing Sb(v) and Mn 2+mentioning
confidence: 99%
“…Adsorption of strong acid anions by metal oxides and hydroxides typically decreases with increasing pH [31]. Such a pH effect was observed for the sorption of As(V) onto iron oxides or iron-containing oxides [32,33]. H 2 AsO Lower pH is favorable for the protonation of the sorbent surface.…”
Section: Effect Of Ph and Ionic Strengthmentioning
confidence: 99%
“…Many of these adsorbents have shown much promise for the removal of phosphate from water. For example, Zhang et al (2009) reported that a Fe-Mn binary oxide had a high P sorption capacity of 36 mg g at pH 5.6. Harver and Rhue (2008) reported that mixed Al-Fe hydr(oxides) were effective for P removal.…”
Section: Introductionmentioning
confidence: 99%